ATRT-21. COMPARATIVE INTEGRATIVE ANALYSIS OF PRIMARY AND RELAPSED ATYPICAL TERATOID/RHABDOID TUMORS (AT/RTs) - Holsten, Till (Neuro Oncol, 2018)
Atypical teratoid/rhabdoid tumor (AT/RT) is an aggressive malignancy of infancy and early childhood representing the most common CNS tumor in children below the age of one year. AT/RTs harbour germline or somatic mutations in SMARCB1 or SMARCA4 while other recurrent genetic alterations are lacking. Though survival rates have slightly improved over the last years, prognosis remains poor, especially in the case of relapse. Our project aims at understanding molecular events contributing to relapse in AT/RT. To this end, histopathological and molecular features (DNA methylation array and whole exome sequencing) of 21 pairs of primary and relapsed AT/RTs were investigated. On histopathological examination, relapsed AT/RTs showed loss of architecture and significantly increased proliferation as compared to primary tumors. Although molecular subgroups did not change at recurrence, global methylation analysis of matched primary and recurrent tumor samples demonstrated an enrichment of differentially methylated areas at transcribed regions and promoters and distinct changes in trimethylation at H3K27 in a fraction of relapsed cases. CNV profiling revealed recurrent gains at multiple regions, while losses preferentially affected histone genes at chromosome 6. Finally, whole exome sequencing discovered a number of mutations affecting more than 3 relapse samples, but not the respective primary lesions. Our findings may contribute to improve the understanding of biological changes leading to enhanced aggressiveness of relapsed AT/RTs and provide a basis for further functional analyses.